Pendekatan SWOT Analisis Dalam Mengukur Tingkat Kualitas Pelayanan di Bkad Kota Bandung - Suryaningsih, Syafni; Sudrartono, Tiris (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Public service is a form of activity provided by the government to the community. Knowing what are the problems that become obstacles in the Bandung City Government Land Lease Service activities in order to find strategies to improve the quality of Bandung City Government Land Lease Services. Also, to find out the efforts that can be made in measuring BKAD customer satisfaction through SWOT analysis. In this study the authors used a qualitative descriptive method. Data collection techniques were carried out using observation techniques, interviews, field observations and documentation. In order to create comfort for the community, with the support of qualified facilities for the community in supporting to convey criticism and aspirations for land lease services to make it easier and more efficient. Keywords: Service; Service Quality; SWOT